Conceptions of Mental Illness and Psychopharmaceuticals in Global Health - Jenkins, Janis H. (Revista de Antropología Social, 2023)
The field of global health has prioritized the scaling up of services and treatment for mental health in low and middle-income countries. While equitable access to treatments constitutes a priority, the call for urgent action to fill the treatment gap has been advanced largely in the absence of an appeal for ethnographic attention to sociocultural knowledge of conditions and their treatment. This article argues that local knowledge of conceptions of mental illness and psychotropic medication is foundational for an informed understanding of treatment in relation to subjective experience, cultural meaning, and clinical efficacy. These issues are specifically explored in relation to scientific, clinical, and popular discourse surrounding the cultural trope of “chemical imbalance.”